Strategi Komunikasi Digital Pemanfaatan Media Sosial Pada Akun Instagram @kopling.sumbawa Dalam Meningkatkan Daya Tarik Konsumen Di Kabupaten Sumbawa - Novita Dwi Wardani; Vivin Nila Rakhmattullah (Jurnal Ilmiah Literasi Indonesia, 2026)
The development of social media has encouraged UMKM to utilize digital platforms as a means of promotion and communication with consumers. One business actor that implements this strategy is the Instagram account @kopling.sumbawa, which is used to introduce products, convey sales location information, and build interactions with consumers in Sumbawa Regency. This study aims to determine how the digital communication strategy implemented by the Instagram account @kopling.sumbawa in increasing consumer appeal. This study uses a descriptive qualitative approach based on Philip R. Smith's Digital Communication Strategy Theory which includes situation analysis, setting communication objectives, compiling messages, selecting media, implementing communication, and evaluating communication. Data collection was conducted through non-participant observation, semi-structured interviews, and documentation of account managers, employees, and consumers of Kopling Sumbawa. The results show that the Instagram account @kopling.sumbawa actively utilizes the feed, reels, and story features to convey product information, sales locations, business atmosphere, and build interactions with consumers. Attractive visual content, the use of simple and communicative language, and consistent uploads are considered capable of increasing consumer interest and strengthening brand awareness. Overall, the implemented digital communication strategy was deemed quite effective in increasing consumer appeal in Sumbawa Regency